Hepatoprotective effects of Yulangsan polysaccharide against nimesulide-induced liver injury in mice. (22nd August 2015) - Nguyen, Vanphuc; Huang, Jianchun; Doan, Vanminh; Lin, Xing; Tang, Xiuneng; Huang, Yuanheng; Tang, Aicun; Yang, Xin; Huang, Renbin
Abstract: Ethnopharmacological relevance: Yulangsan polysaccharide (YLSPS) is often used in popular folk medicine in the Guangxi Zhuang Autonomous Region of China as a chief ingredient of Millettia pulchra, which is used as a hepatic protection, anti-aging and memory improving agent. Aim of the study: This study was designed to investigate the protective effects of polysaccharides from Millettia pulchra Kurz var.laxior (Dunn) (Yulangsan polysaecharide, YLSPS) against nimesulide-induced hepatotoxicities in mice. Materials and methods: Liver injury was induced in mice by administering nimesulide. Simultaneously, YLSPS was administered 2 h prior to the administration of nimesulide. Dimethyl diphenyl bicarboxylate (DDB) was used as a reference drug. Results: Compared with the nimesulide group, YLSPS significantly decreased the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and the content of bilirubin in the serum. The anti-oxidative effect of YLSPS was observed from the increase of the superoxide dismutase (SOD) and catalase and glutathione peroxidase (GSH-Px) activities in the liver, both of which were decreased by nimesulide. Moreover, the content of malondialdehyde (MDA) was reduced, and histological findings also confirmed the anti-hepatotoxic activity. In addition, YLSPS significantly inhibited proinflammatory mediators, such as tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6). Additionally, YLSPS also enhanced the mitochondrial antioxidant and inhibited dead cells by preventing the down-regulation of Bcl-2, up-regulation and release of Bax along with caspase 9 and 3 activity, confirming the involvement of mitochondria in the nimesulide-induced apoptosis. Conclusion: The protective effect of YLSPS against nimesulide-induced hepatic injury may rely on its ability to reduce oxidative stress and prevent nimesulide-induced hepatotoxicity by inhibiting critical control points of apoptosis. Graphical abstract: